Systematic analysis of the quench process performance and simulation of the 9.4 T-800 mm whole-body MRI magnet. (23rd February 2023) - Chen, Shunzhong; Wang, Lei; Zhang, Zili; Wang, Yaohui; Wang, Hui; Cheng, Junsheng; Dai, Yinming; Wang, Qiuliang
Abstract: In 2021, the Institute of Electrical Engineering, Chinese Academy of Sciences successfully reached 9.4 T in a whole-body magnetic resonance imaging (MRI) superconducting magnet with an inner diameter of 800 mm. In this study, a systematic analysis of both the real quench protection performance and a simulation are reported. The four successful quench protections during the entire energization process proved the feasibility of the 'in-out-in' quench protection protocol for a 9.4 T-800 mm superconducting magnet. The quench trigger sequence was shown to be adjusted by changing the heater thickness, which demonstrates the flexibility of the 'in-out-in' quench protection protocol to fit a different MRI magnet design. The high accuracy of the quench protection simulation method and code was confirmed through comparison of the simulation results with the real performance. Moreover, the limitations of the current quench protection and reference value to other MRI magnets were discussed. It is believed that this study will be useful to other research groups and promote the development of an extremely high-field whole-body MRI system.